Transplant-ineligible newly diagnosed multiple myeloma: current and future approaches to clinical care; a young International society of geriatric oncology review paper - Grant, Shakira J.; Mian, Hira S.; Giri, Smith; Boutin, Melina; Dottorini, Lorenzo; Neuendorff, Nina Rosa; Krok-Schoen, Jessica L.; Nikita, Nikita; Rosko, Ashley E.; Wildes, Tanya M.; Zweegman, Sonja (Journal of geriatric oncology, 2021)
Multiple myeloma is the second most common hematological malignancy in the USA and Europe. Despite improvements in the 5-year and overall survival rates over the past decade, older adults (aged ≥65 years) with multiple myeloma continue to experience disproportionately worse outcomes than their younger counterparts. These differences in outcomes arise from the increased prevalence of vulnerabilities such as medical comorbidities and frailty seen with advancing age that can influence treatment-delivery and tolerance and impact survival. In general, geriatric assessments can help identify those patients more likely to benefit from enhanced toxicity risk-prediction and aid treatment decision-making. Despite the observed benefits of geriatric assessments and other screening frailty tools, provider and systems-level barriers continue to influence the overall perception of the feasibility of geriatric assessments in clinical practice settings. Clinical trials are underway evaluating the efficacy and safety of various multiple myeloma therapies in less fit/frail older adults, with a minority examining fitness-based/risk-adapted approaches. Thus, significant gaps exist in knowing which myeloma therapies are most appropriate for older and more vulnerable adults with multiple myeloma. The purpose of this Review is to discuss how geriatric assessments can be used to guide the management of transplant-ineligible patients; and to highlight frontline therapies for standard-risk and high-risk cytogenetic abnormalities [i.e., t(4;14), t(14;16), and del(17p)] associated with multiple myeloma. We also discuss the current shortcomings of the existing clinical approaches to care and highlight ongoing clinical trials evaluating newer fitness-based approaches to managing transplant-ineligible patients.
Available online 17 December 2020
Gesehen am 29.07.2021